2009
DOI: 10.1111/j.1365-2486.2009.01922.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of south European Atlantic salmon under global change

Abstract: Populations at the edge of species distributions are especially vulnerable to climate change. Genetic changes as well as modification of their population structure are expected as reactions to global warming. Atlantic salmon (Salmo salar) inhabiting south France has been chosen as a model for studying the effect of global warming in marginal populations during the last 15 years. Increased gene flow between neighboring populations and dichotomy of maturation age between sexes have been identified as two main po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 69 publications
2
28
0
Order By: Relevance
“…Long datasets of well-monitored populations (survival at hatching, juvenile growth, smolt age, age at maturity, fertility and many other traits) could serve for this purpose, and would facilitate investigation of the association of population data with various climate indices (NAOI, Atlantic Multidecadal Oscillation, others). Between-river migration of adults, or straying and entering a nonnatal river when returning from the sea, are possibilities; research by Valiente et al (2010) for another region at the same latitude demonstrated that warm conditions enhanced straying, contributing to increased gene flow. Valiente et al (2010) also reported indirect signals of increased contribution of freshwatermaturing males (juvenile-like or precocious parr) under warmer climate conditions; such a finding suggests that an increased contribution to spawning by mature male parr of foreign origin, which are known to be responsible for at least some genome introgression at this latitude (Moran et al, 1994), may also play a role in eroding population structuring.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Long datasets of well-monitored populations (survival at hatching, juvenile growth, smolt age, age at maturity, fertility and many other traits) could serve for this purpose, and would facilitate investigation of the association of population data with various climate indices (NAOI, Atlantic Multidecadal Oscillation, others). Between-river migration of adults, or straying and entering a nonnatal river when returning from the sea, are possibilities; research by Valiente et al (2010) for another region at the same latitude demonstrated that warm conditions enhanced straying, contributing to increased gene flow. Valiente et al (2010) also reported indirect signals of increased contribution of freshwatermaturing males (juvenile-like or precocious parr) under warmer climate conditions; such a finding suggests that an increased contribution to spawning by mature male parr of foreign origin, which are known to be responsible for at least some genome introgression at this latitude (Moran et al, 1994), may also play a role in eroding population structuring.…”
Section: Discussionmentioning
confidence: 99%
“…Between-river migration of adults, or straying and entering a nonnatal river when returning from the sea, are possibilities; research by Valiente et al (2010) for another region at the same latitude demonstrated that warm conditions enhanced straying, contributing to increased gene flow. Valiente et al (2010) also reported indirect signals of increased contribution of freshwatermaturing males (juvenile-like or precocious parr) under warmer climate conditions; such a finding suggests that an increased contribution to spawning by mature male parr of foreign origin, which are known to be responsible for at least some genome introgression at this latitude (Moran et al, 1994), may also play a role in eroding population structuring. Thus, synergistic effects related to a warmer climate may act to accelerate the homogenizing effect of human-mediated introgression, even after the cessation of introductions of foreign stocks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…through changes in the geographical distributions of temperature-sensitive species (Thomas et al 2004), predator-prey relationships (Parmesan 2006), generation time (Gross 2011) and population structuring (Horreo et al 2011), or through asynchrony of life histories by delayed or advanced migrations (Valiente et al 2010), through replacement of a species by another with different environmental requirements (Erasmus et al 2002, Wilson et al 2007). In intertidal ecosystems, species diversity and composition change along with climate, more pronouncedly in the most recent decades (Helmuth et al 2006).…”
Section: Introductionmentioning
confidence: 99%